Maternal Predictors of Disparate Outcomes in Children With Single Ventricle Congenital Heart Disease. Issue 12 (16th June 2020) - Asrani, Priyanka; Pinto, Nelangi M.; Puchalski, Michael D.; Ou, Zhining; Silver, Robert M.; Zinkhan, Erin K.; Heuser, Cara C.; Nance, Amy; Miller, Thomas A.
Abstract : Background: Significant variability in morbidity and mortality persists for children with functionally single ventricle congenital heart disease (SV‐CHD) despite standardization in medical and surgical care. We hypothesized that maternal health factors may be associated with an increased risk of poor outcomes in children with SV‐CHD. Methods and Results: This retrospective, observational, cohort study included term maternal‐infant pairs with a diagnosis of SV‐CHD who underwent surgical palliation from 2006 to 2015 at Primary Children's Hospital. Pairs lacking maternal variables of interest or infant follow‐up data were excluded. The association of maternal risk factors of abnormal pre‐pregnancy body mass index, abnormal gestational weight gain (<7 or >20 kg), hypertensive disorders, and gestational diabetes mellitus with death/transplant and hemodynamics were analyzed using regression models. Of 190 infants, 135 (71%) maternal‐infant dyads had complete data for inclusion. Death or transplant occurred in 48 infants (36%) during an average follow‐up of 2.2 years (0.1–11.7 years). Abnormal gestational weight gain was associated with an increased risk of death and/or transplant in logistic regression (odds ratio, 3.22; 95% CI, 1.32–7.86; P =0.01), but not Cox regression (hazard ratio, 1.9; 95% CI, 1.0–3.7; P =0.055). Mean pulmonary artery pressures were higher in the setting of abnormal gestational weight gain (16.5±2.9 versus 14.7±3.0 mm Hg; P <0.001), and abnormal pre‐pregnancy body mass index (15.7±3.5 versus 14.2±2.1 mm Hg; P <0.001) in the systemic right ventricle group. Conclusions: Abnormal gestational weight gain (excessive or inadequate) is a novel risk factor for worse outcomes in SV‐CHD. The fetoplacental environment may alter the trajectory of vascular development to impact outcomes in infants with SV‐CHD.